Avaliaç\~ao dos efeitos econômicos dos Fundos Constitucionais de Financiamento do Nordeste, do Norte e do Centro-Oeste: Uma análise por tipologia da política nacional de desenvolvimento regional entre 1999 e 2011 - Guilherme Mendes Resende; Diego Firmino Costa da Silva; Luís Abel da Silva Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This paper seeks to evaluate the relationship between the Brazilian Regional Development Funds and GDP per capita growth on two spatial scales (municipalities and micro-regions) between 1999 and 2011. In addition to the multi-scalar approach, this work brings to the available literature three contributions: i) the study of a longer period (1999-2011) compared to the previous literature; ii) the possibility of spatial interaction between the geographical units, which has the advantage of allowing the analysis of the direct and indirect effects (spillover effects); and iii) the consideration of heterogeneity institutionalized by the National Policy for Regional Development (PNDR) through the typology defined by this policy. The results of non-spatial panel fixed effects models showed that resources allocated to the Dynamic and Low-Income typologies have positive impact on GDP per capita growth for both spatial scales (municipal and micro-regional levels) in the Northeast, reinforcing the evidence of the role played by the FNE on reducing inequalities at macro-regional and intra-regional levels. Regarding the FNO, the results show evidence of positive effects of FNO on GDP per capita growth at municipal level for dynamic and high-income types. With regard to the FCO, the results show that the resources present, for high-income type, positive effects on GDP per capita growth at the municipal level. Finally, when investigating the spatial dependence, it was found that this should be taken into account in the study of the effect of these funds.
Keywords: C52; R58; 330; regional policy; constitutional financing funds; regional disparities; impact evaluation; spatial spillovers